Antinociceptive Effects of Paeonia daurica subsp. macrophylla Root Extracts in Mice - Hamidreza Monsef-Esfahani; Sahand Jamshidi; Paria Sharafi-Badr; Mohammad Sharifzadeh; Mahdi Vazirian; Seyede Nargess Sadati Lamardi (Tehran University of Medical Sciences, 2023)
This study aimed to assess the antinociceptive activity of extracts and fractions of Paeonia daurica subsp. macrophylla in BALB/c mice. Various doses of hydro-alcoholic extract (HE), hexane fraction (F-hexane), methanol (F-MeOH), and chloroform (F-CHCl3), as well as aqueous extracts (AE), were evaluated by a well-known model, a formalin-induced pain test in mice. All extracts, piroxicam 0.1 mg/kg, and negative control groups were administered 30 minutes before formalin injection. Flinching, licking, and biting reflexes were measured as painful factors compared with controls at intervals of 0 to 5 minutes, 0 to 15, and 0 to 60 minutes after formalin injection. The acute oral toxicity test of total ethanolic and aqueous extracts showed no signs of toxic effect up to a dose of 5000 mg/kg. In the formalin test at a time interval of 0 to 5 minutes, there was no significant difference between the results of the study groups. In the range of 0 to 15 minutes, the effect of AE (1 g/kg), HE (2, 3 g/kg), and F-hexane (1 g/kg) was significantly higher than the positive control group (p<0.01). In the time interval of 0 to 60 minutes as the total time of the experiment, the effect of AE (0.25 g/kg), AE (0.5, 1 g/kg), HE (2, 3 g/kg), F-hexane (1 g/kg) were significantly different than the positive control group. It can be concluded that extract of P. daurica ssp. macrophylla might be helpful in the treatment of pain in humans.